Postmortem distribution of acephate and its metabolite methamidophos in body fluids and organ tissues of an intoxication case. (July 2019) - Takayasu, Tatsunori; Yamamoto, Hiroki; Ishida, Yuko; Nosaka, Mizuho; Kuninaka, Yumi; Shimada, Emi; Kawaguchi, Mariko; Kimura, Akihiko; Kondo, Toshikazu
Highlights: This report an intoxication case caused by the ingestion of the pesticide Ortoran ®, which consists of 50% acephate. Based on these results and autopsy findings, the cause of death was acute fatal intoxication caused by the pesticide. A high relative concentration of brain methamidophos may contribute to the intoxication of acephate in humans. Abstract: We herein report an intoxication case caused by the ingestion of the pesticide Ortoran ®, which consists of 50% acephate aqueous solution. A man in his 60 s was found dead in his car with a 100-mL bottle containing approximately 50 mL of Ortoran ® . In a gas chromatography – mass spectrometry (GC–MS) screening test, acephate and its metabolite methamidophos were qualitatively detected in his stomach contents. The amounts of acephate and methamidophos (μg/g) in the extract of each body fluid or organ tissue were measured using GC–MS and were as follows: 35.8, 2.84 (heart blood); 44.0, 2.26 (peripheral blood); 2, 240, 2.79 (urine); 53.1, 8.91 (brain occipital lobe); 43.7, 2.95 (liver); 102.3, 8.02 (right kidney); and 5450, 22.9 (stomach contents). Based on these results and autopsy findings, the cause of death was concluded to be acute fatal intoxication caused by the pesticide containing acephate and its active metabolite, methamidophos. Concentration ratios between acephate and methamidophos in each body fluid and organ tissue showed higher relative concentrations of brain methamidophos to acephate than those of other organ tissues. A high relative concentration of brain methamidophos may contribute to the intoxication of acephate in humans.